(untitled) (Research, Society and Development, 2020)
Objective: To analyze the occupational routine of mothers accompanying premature babies admitted to the neonatal unit. Methodology: This is a descriptive, qualitative study, developed at Maternal Accommodation, from May to August 2019, with the participation of 12 accompanying mothers who had a minimum stay of 15 days. Results: From the process of analyzing the content of the reports, the categories were created: pre and postpartum routines, support network and values/beliefs/spirituality and work activities. Conclusion: It was observed that the permanence in the maternal accommodation and the demand for being in the neonatal unit is tiring and exhausting for the woman, especially in addition to concerns about responsibilities with other family members. It was noted that the newborn’s hospitalization especially affects the mother, leading to an exhaustive routine, which points to the need for further studies on the routine management of these mothers and on the care provided to her.